2019
DOI: 10.2478/limre-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

A shallow lake in an agricultural landscape – water quality, nutrient loads, future management

Abstract: Qualitative analyses of nitrogen and phosphorus loads reaching the lake ecosystem provide a basis for pollution control, which is of paramount importance in shallow lakes due to the rapid turn-over of matter and energy. The studies of both external and internal loading were conducted in Lake Łeknenskie, a very shallow, through-flow lake situated in Western Poland. Strong eutrophication is manifested in rich rush vegetation and a lack of submerged macrophytes as well as nitrogen and phosphorus concentrations (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…The presented studies have shown that small water bodies with bathing waters were significantly less frequently monitored in all the referred monitoring programs. The reason for this in Poland is the law regulation requiring that only lakes larger than 50 ha might be monitored in the national SMS system coordinated by CIEP (Ciecierska and Kolada 2014 ; Dondajewska et al 2019 ). Thus, small lakes, ponds, and other water reservoirs used for bathing did not have a chance to be investigated in detail, unlike the larger lakes, in accordance with the WFD in EU countries.…”
Section: Discussionmentioning
confidence: 99%
“…The presented studies have shown that small water bodies with bathing waters were significantly less frequently monitored in all the referred monitoring programs. The reason for this in Poland is the law regulation requiring that only lakes larger than 50 ha might be monitored in the national SMS system coordinated by CIEP (Ciecierska and Kolada 2014 ; Dondajewska et al 2019 ). Thus, small lakes, ponds, and other water reservoirs used for bathing did not have a chance to be investigated in detail, unlike the larger lakes, in accordance with the WFD in EU countries.…”
Section: Discussionmentioning
confidence: 99%
“…Hill, 1991 has been identified as contributing to red tide events in many countries (Yoo et al 2017). The C. curvata has been associated with high levels of dissolved total phosphorus and dissolved total nitrogen (Xia et al 2014;Dondajewska et al 2019).…”
Section: Taxonomic Distribution Of Microbial Populationmentioning
confidence: 99%
“…Eutrophication is one of the well-described impacts of the present time, almost always associated with the increase in cyanobacteria biomass and a drastic reduction of submerged macrophytes (Dondajewska et al, 2019), besides the simplification of the trophic structure, loss of biodiversity and species extinction (Dubey and Dutta, 2020). Therefore, an increase of nutrients is directly associated with the primary production increase and, consequently excessive growth of algae (Ballah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%